Environmental interests in investment arbitration challenges and directions - Marisi, Flavia (International arbitration law library ;, 2020)
Environmental Interests in Investment Arbitration examines the legal framework for environmental interests in investment law, with the purpose of reaching a balance between the protection of foreign investments and the protection of the environment. Economic growth, social inclusion, and environmental protection stand at the core of sustainable development, which aims to deliver long-term growth for current and future generations. Foreign Direct Investment (FDI) can play a key role in sustainable development. Host States? benefits descending from FDI inflows include tax revenues, technology transfer, specialised training of local human resources, network with satellite activities, better availability of quality products and customer-centric services, and these downstream effects stimulate economic growth and social inclusion. This thoroughly researched book explores the relationship between environmental protection? the third component of sustainable development - and FDI. In recent years, an increasing number of investment arbitration cases have seen a clash between the states? commitments towards their citizens, which include the duty to protect the environment, their health and wellbeing, and the commitment towards foreign investors to protect their investments. The author focuses on investor-state cases in which environmental protection measures have been contested and discusses substantive mechanisms in treaty drafting, rules of Customary International Law, and interpretation doctrines, which are aimed at taking environmental concerns into consideration.